RELATIONSHIP OF TEACHER COMPETENCY TEST AND TEACHER PERFORMANCE ASSESSMENT IN INCREASING EDUCATION QUALITY - EFRILIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Teacher competence is indeed an ability possessed by a professional educator in the field of education in improving the quality of education, of course it needs to be tested and assessment of teacher performance is needed to see the teacher competency profile in order to see the root causes of the problems being faced in order to improve the quality of education. The results of the UKG are also used as material for policy considerations in the provision of teacher professional development and development programs as well as giving awards and appreciation to teachers The results of the Teacher Performance Assessment are used for policy makers and decisions to determine strategic steps in order to improve the quality of teacher performance and more specifically improve the quality of learning and learning services. Hope with the improvement in the quality of the process of providing learning and learning will improve the quality of education.